Pencemaran Tanah dan Air Tanah oleh Pestisida dan Cara Menanggulanginya - Rachman Sutanto (Jurnal Perlindungan Tanaman Indonesia, 2001)
The large increase in the use of modern agricultural chemicals, including pesticides and fertilizers has made agriculture an important non-point source of soil and groundwater contamination. Nitrogen, heavy metals, and organic associated with pesticides are presumably the most common contaminants introduced into the environment by modern agricultural practices. The present and abundance of the chemical contaminants in the soil and underlying groundwater largely depends on their chemical species as well as the various physical, biological and chemical properties of the soil. Understanding these processes and interactions between the contaminants and soil constituents would be useful in identifying effective techniques to restore the soil and groundwater contaminated by modern agricultural practices and others modern society activities. When the level of these contaminants in the soil are such that the quality of the plants, food crops and the groundwater are being compromised, then remedial actions are necessary. Such remediation could include in situ technologies, including bioremediation or phytoremediation combined as well as agronomic-types approaches. The best strategy in reducing soil contamination is to reduce pollution at the source and to use best management practices, such as adopting the most appropriate land use for a given type of soil contamination.